The past, present, and future of theologies of interreligious dialogue - Merrigan, Terrence; Friday, John R. (Oxford University Press, 2017)
The Past, Present and Future of Theology of Interreligious Dialogue' brings together several of the most widely regarded specialists who have contributed to theological reflection on religious diversity and interreligious encounter. The chapters are united by the consistent theme of the obligation to engage with the challenges that emerge from the tension between the doctrinal tradition(s) of Christianity and the need to reconsider them in light of and in response to the fact of religious otherness. As a whole, these reflections are motivated by the desire to bring together a significant selection of different theological approaches that have been developed and appropriated in order to engage with religious difference in the past and present, as well as to suggest possibilities for the future. This confluence of perspectives reveals the complexity of theological reflection on religious diversity, and gives some indication of future challenges that must be acknowledged, and perhaps successfully met, in the ongoing attempt to address a universal reality in light of traditional doctrinal particularities and cultural concerns